2017
DOI: 10.21608/esj.2017.6754
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Revision of Lumbar Interbody Fusion Cages Migration: Clinical Case Series and Literature Review

Abstract: Background Data: Revision surgery for lumbar interbody cage migration is technically demanding.Cage related complication may lead to failure of fusion. Revision of such morbidity is associated with increased risk of permanent neurological insult. Purpose: To analyze the efficacy of posterior approach and iliac crest auto grafting technique in revision of migrated intervertebral cages. Study Design: Retrospective descriptive clinical case study. , we operated 106 patients underwent posterior lumbar interbody fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…They showed fusion rates of 88.24% in patients with bone grafts only, 93.55% when using titanium cages and 100% with PEEK cages. Galhom et al, 16 studied 106 patient underwent TLIF and found Cage migration incidence was 11.3%, with subsidence (6.7%), and retropulsion (4.6%) of all patients.…”
Section: Discussionmentioning
confidence: 99%
“…They showed fusion rates of 88.24% in patients with bone grafts only, 93.55% when using titanium cages and 100% with PEEK cages. Galhom et al, 16 studied 106 patient underwent TLIF and found Cage migration incidence was 11.3%, with subsidence (6.7%), and retropulsion (4.6%) of all patients.…”
Section: Discussionmentioning
confidence: 99%